PEMBELAJARAN IPS MENGGUNAKAN PENDEKATAN KOOPERATIF TIPE GROUP INVESTIGATION DI SEKOLAH DASAR - RAIS, ALFADLI (Universitas Negeri Padang, 2014)
AbstractThe aim of research is to describe the improvement of student’s social science learning outcome by using the group investigation of cooperative tipe at the fourth grade of SDN 11 Sungai Geringging. The design of the research was class action research by using both qualitative aprroch. The subjects of the research were the teacher and sixteen fourth grade student. The data analisis shows that students’ learningoutcome in cycle I was 66.7. the score increased in cycle II into 80. It is concluded that the group investigation of the cooperative type improves students’ social science learningKata kunci: hasil belajar, IPS,pendekatanGroup Investigation